Revisiting the Perfluorinated Trityl Cation. Issue 20 (4th March 2019) - Delany, Eoghan G.; Kaur, Satnam; Cummings, Steven; Basse, Kristoffer; Wilson, David J. D.; Dutton, Jason L.
Abstract: Although ultimately not isolable for X‐ray structural characterization, the free perfluorinated trityl cation was shown to be observable in neat triflic acid, which represents milder conditions than previous reports of this cation in "magic acid" or oleum. A triflate‐bound species could be generated in organic solvents using stoichiometric amounts of triflic acid and was shown to be synthetically viable for hydride abstraction from Et3 SiH. It was demonstrated that the para ‐position on the ‐C6 F5 rings is the primary point of attack for decomposition of the cation. Abstract : Blast from the past . A triflate bound derivative of the perfluorinated trityl cation can be generated from triflic acid in organic solvent at −20 °C and used as a hydride acceptor. The free cation can also be observed in neat triflic acid. Attack on the para ‐carbon by nucleophiles is the primary mode of decomposition of the cation.